New Univariate Synthetic Double Sampling X And Multivariate Synthetic Double Sampling T2 Control Charts - Lee, How Chinh (2017)
This thesis proposes a univariate synthetic double sampling X control chart to monitor the mean of a univariate process and a multivariate synthetic double sampling 2 T control chart for monitoring the mean vector of a multivariate process. The proposed univariate chart integrates the conforming run length (CRL) chart and the double sampling (DS) X chart, while the proposed multivariate chart combines the CRL chart and the DS 2 T chart. Both the proposed univariate and multivariate charts are superior to their basic counterparts, namely the synthetic X and DS X charts for the univariate case, and the synthetic 2 T and DS 2 T charts for the multivariate case,